The development of pre-service teachers’ self-efficacy in teaching mathematics - Bjerke, Annette Hessen (NOMAD Nordic Studies in Mathematics Education, 2017)
Teacher efficacy has received much attention in the general field of educational research, but applications in mathematics teacher education are few. In order to deepen the understanding of the nature and development of self-efficacy in teaching mathematics (SETM) during teacher education, the study presented here followed over a period of two years pre-service teachers (PSTs) preparing to teach primary school mathematics in Norway (grades 1–7, ages 6–13). Their developing SETM was investigated by means of an instrument designed to target the core activity of teaching mathematics: helping a generic child with mathematics tasks. A comparison of responses collected from 191 novice PSTs with those from the same cohort two years later (n = 103) shows a rise in SETM in the typical PST, and indicates the nature of the development of SETM during teacher education.